The Influence of Influencer Credibility on the Intention to Visit a Culinary Event in Bandar Lampung - Maesa, Jennie Anggraeni; Roslina (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
Business development in Indonesia today can be considered very rapid in the culinary or food sector, this makes business people to present various new culinary concepts that combine tradition with innovation, namely by holding culinary events or festivals. The event must carry out promotional activities to attract visitors to buy and visit the culinary event. In this era, social media influencers play an important role in marketing by introducing products to their followers. An influencer must have credibility to be able to attract interest from their followers so that they have the intention to visit the promoted product. This study analyzes the influence of the credibility of influencers @kuliner_lampung which has the dimensions of trustworthiness, expertise, similarity, and attractiveness on the intention to visit culinary events in Bandar Lampung studies on Instagram Followers @Kuliner_Lampung. The data used in this study are primary data obtained from the results of respondents' answers collected by distributing questionnaires. The sample in this study were 133 respondents, taken using the Nonprobability Sampling method using Purposive Sampling technique. This study uses multiple linear regression analysis and partial hypothesis testing (t-test). The results obtained in this study indicate that trustworthiness, expertise, similarity, and attractiveness on influencers @kuliner_lampung have a positive and significant effect on the intention to visit culinary events in Bandar Lampung.